Effect of Front Line Demonstrations on Yield of Field Pea in Ghazipur District of Uttar Pradesh - A.P. Diwedi, V. Diwedi, R.P. Singh,Mamta Singh, D.R. Singh (Indian Journal of Extension Education, 2022)
Field Pea (Pisum sativum L.), also called as poisproteagineux in French,guisante in. Spanish, pisello inItalian, futtererbse in German and matter in Hindi, is animportant winter season grain legume crop largely confinedto cooler temperate zone. These are two types ofcultivated pea i.e. garden pea and field pea. Garden peasareharvested in an immature conditions and cooked asfresh or canned for subsequence uses. Field Pea isgenerally grown for dry seeds which are used for a varietyof snack preparation and dal. The mature pea is highlynutritive containing high proportion of digestive protein(22.5%), carbohydrates ( 62.1 %), fat (1.8%), minerals(calcium, iron) and vitamins (Riboflavin, thiamin etc.). Themost probable centre of origin of pea is Mediterraneanregion of Europe and central Asia.